The case for standing X-rays: Clinical indications for weight-bearing lumbar spine imaging in younger athletic populations presenting with chronic lower back pain. (April 2015) - Inklebarger, James; Clarke, Timothy P.
<x content-type="archive" xml:space="preserve">Abstract</x> Weight-bearing lumbar spine X-rays have confirmed diagnostic utility in identifying structural spinal pathologies and postural dysfunctions, which may otherwise be underestimated by recumbent studies. This is particularly true in the sub-population of young athletes with chronic lower back pain in whom spondylolysis and listhesis is suspected. In consideration of the relatively higher ionizing radiation doses associated with lumbar imaging, some United Kingdom consultation groups have narrowed the criteria to exclude lumbar X-ray for young athletic populations with chronic low back pain. This has posed challenges for orthopaedic clinicians, who consider weight bearing lumbar spine X-rays as a first-line and cost-effective alternative to lumbar magnetic resonance imaging, to exclude spondylolysis and listhesis and ankylosing spondylitis in younger populations, for grading and monitoring scoliosis, and for other reasons. Unfortunately, these 'recumbent view only' policies may run contrary to known techniques for reducing ionizing radiation exposure, such as increasing the source-to-image distance; and the higher comparative levels of ionizing radiation assumed with lumbar imaging in relation to chest X-ray may have been overestimated.